2019
DOI: 10.1002/lno.11348
|View full text |Cite
|
Sign up to set email alerts
|

Euphotic zone nitrification in the California Current Ecosystem

Abstract: Nitrification, the microbial conversion of ammonium to nitrite then to nitrate, occurs throughout the oceanic water column, yet the environmental factors influencing the production of nitrate in the euphotic zone (EZ) remain unclear. In this study, the natural abundances of N and O isotopes (δ 15 N and δ 18 O, respectively) in nitrate were used in an existing model framework to quantify nitrate contributed by EZ nitrification in the California Current Ecosystem (CCE) during two anomalously warm years. Model da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 82 publications
(175 reference statements)
2
16
0
Order By: Relevance
“…This was calculated using trapezoidal integration of two values in the lower euphotic zone, potentially introducing error into the estimates; however, this error is likely minimal as values were integrated over a narrow depth range and nitrification decreases exponentially with depth below the euphotic zone. Estimates of the contribution of nitrification to phytoplankton N demand in this study are consistent with values previously reported for the CC system (6–36%; Wankel et al 2007; Stephens et al 2019). The higher contribution of nitrification to the euphotic zone nitrate reservoir in fall suggests that regenerated production is of greater importance during weak upwelling when both primary production and new production are expected to be at a minimum, consistent with a meta‐analysis of nitrification and primary production rates that found an inverse relationship between primary production and the fraction of phytoplankton N demand supplied by nitrification (Peng et al 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was calculated using trapezoidal integration of two values in the lower euphotic zone, potentially introducing error into the estimates; however, this error is likely minimal as values were integrated over a narrow depth range and nitrification decreases exponentially with depth below the euphotic zone. Estimates of the contribution of nitrification to phytoplankton N demand in this study are consistent with values previously reported for the CC system (6–36%; Wankel et al 2007; Stephens et al 2019). The higher contribution of nitrification to the euphotic zone nitrate reservoir in fall suggests that regenerated production is of greater importance during weak upwelling when both primary production and new production are expected to be at a minimum, consistent with a meta‐analysis of nitrification and primary production rates that found an inverse relationship between primary production and the fraction of phytoplankton N demand supplied by nitrification (Peng et al 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Many studies report measurable rates of marine nitrification in the euphotic zone (Ward 2005; Clark et al 2007; Peng et al 2018), and nitrification is increasingly considered an important source of nitrate fueling primary production in the surface ocean (Yool et al 2007; Stephens et al 2019). Nitrification is often thought to be inhibited by light and to only occur in waters below the euphotic zone (Merbt et al 2012).…”
Section: Figmentioning
confidence: 99%
“…New production was then computed as primary productivity/6.625 × f‐ratio. New production measurements based on 15 NO3 uptake can overestimate true nitrate uptake if substantial euphotic zone nitrification occurs, although this issue appears to be minor in the CCE (Stephens et al., 2020; Yool et al., 2007) Sinking carbon vertical fluxes were measured using 238 U − 234 Th disequilibrium and surface‐tethered drifting sediment traps positioned at the base of the euphotic zone (Stukel & Barbeau, 2020; Stukel et al., 2019). Sinking particle flux was typically measured 20–40 m beneath the depth of the euphotic zone.…”
Section: Data Set and Methodsmentioning
confidence: 99%
“…Previous studies in the CCE have shown that new production (i.e., production based on upwelled nitrate) tends to exceed carbon exported vertically below the euphotic zone in the nearshore region, where new and primary production is maximal (Chavez et al., 1991; Kranz et al., 2020; Plattner et al., 2005; Stukel et al., 2011). This imbalance is reduced and possibly compensated further offshore (Stephens et al., 2020; Stukel et al., 2011), with lower than expected vertical carbon export close to shore and higher than expected vertical carbon export further offshore. A hypothesis that would explain this spatial imbalance is that inorganic carbon is fixed in the nearshore region and then exported by the cross‐shore circulation from nearshore sites of production to offshore sites of export.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, nitrification in the surface layer is limited by the photoinhibition of nitrifying microorganisms and competition with phytoplankton for ammonia (Lomas and Lipschultz, 2006). Several studies have suggested the possibility of nitrification within the euphotic zone (Wankel et al, 2007;Rafter and Sigman, 2016;Stephens et al, 2020). Therefore, DN 2 O-AOU and NO − 3 correlations suggested that the slightly supersaturated N 2 O of the surface layer during this investigation may be due to the products derived from nitrification within the euphotic zone, and gradually increasing nitrification near the boundary of the euphotic zone.…”
Section: Hydrographic Conditions In the Stwnpomentioning
confidence: 99%